2017
DOI: 10.1017/s0950268817002400
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and antimicrobial resistance ofSalmonelladiarrhoeal infection among children in Thi-Qar Governorate, Iraq

Abstract: We conducted a hospital-based cross-sectional study among children aged <5 years in Thi-Qar Governorate, south-eastern Iraq, in order to examine the prevalence, risk factors and antimicrobial resistance associated with gastroenteritis caused by Salmonella infection. From 320 diarrhoea cases enrolled between March and August 2016, 33 (10·3%, 95% confidence interval (CI) 8·4-12·4) cases were stool culture-positive for non-typhoidal Salmonella enterica. The most commonly identified serovar was Typhimurium (54%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 37 publications
(41 reference statements)
7
24
0
Order By: Relevance
“…In our study, S. typhimurium was the predominant subtype identified in both NTS (38.9%) and iNTS (47.4%) groups. Similar to our results, studies from Kenya (59%) (16) and Iraq (54.5%) (23), reported that S. typhimurium was the predominant subtype of the NTS isolated, however with slightly higher rates. In our study, S. enteritidis (29.6%) was the second common subtype identified among the NTS isolated from stool samples.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, S. typhimurium was the predominant subtype identified in both NTS (38.9%) and iNTS (47.4%) groups. Similar to our results, studies from Kenya (59%) (16) and Iraq (54.5%) (23), reported that S. typhimurium was the predominant subtype of the NTS isolated, however with slightly higher rates. In our study, S. enteritidis (29.6%) was the second common subtype identified among the NTS isolated from stool samples.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies from West Africa (31) and Malaysia (35) reported 100% susceptibility to ciprofloxacin. We reported that 41.3% of our isolates were resistant to cefotaxime, which was higher than that reported from India (32.5%) (22), Congo (2.1%) (33), Southwest China (11.9%) (27), and comparable to that reported from Iraq (42.4%) (23). Gentamicin resistance was reported to be 39.1% among our isolates, while studies from Ethiopia (7.5%) (34), Southwest China (11.9%) (27), reported lower and a study from India (40%) (22), reported a comparable rate of resistance to gentamicin.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Among the bacterial etiology of diarrhea, non-typhoidal Salmonella (NTS) is one of the major zoonotic pathogens reported in children, transmitted by ingestion of contaminated food or water and by contact with animals or poultry [3][4][5]. Among more than 2500 Salmonella serovars, Salmonella enterica serovar Typhimurium (S. Typhimurium) and S. Enteritidis are two most common serotypes associated with NTS gastroenteritis in children across the globe [5][6][7][8][9][10][11][12][13]. Low immunity, immature endogenous bowel flora, and gastric hypoacidity in Responsible Editor: Tânia A. Tardelli Gomes.…”
Section: Introductionmentioning
confidence: 99%